Thomas Dunn papers - Dunn, Thomas, -1916.
Correspondence, business records, and receipts from Olyphant & Company for duties received from the superintendent of customs in Fu-chou shih, Fukien Province, China (Foochow). Includes letters from S. Wells Williams, U.S. Legation, Macao and Shanghai, relating to the Treaty of Tientsin (1858) ending the first part of the second Opium War, customs, and the Chinese empire; and letters, documents, real estate papers, and other business papers (1909-1918) prepared by John C. Oswald, Dunn's agent, concerning Dunn's property and the settlement of his estate in Fu-chou shih.
Diplomat and businessman.
Collection material in English.
Keywords: Oswald, John C; Williams, S. Wells -- 1812-1884 -- Correspondence; Olyphant & Company; Customs administration -- China; Diplomatic and consular service, American -- China; Diplomatic and consular service, American -- China -- Macau (Special Administrative Region); China -- Foreign relations -- Treaties; China -- Foreign relations -- United States; Opium trade -- China -- History; China -- History -- 1795-1861.; Fuzhou Shi (Fujian Sheng, China) -- History; Macau (China : Special Administrative Region) -- History; Shanghai (China) -- History; United States -- Foreign relations -- China; Businessmen; Diplomats